Current therapeutic vaccination and immunotherapy strategies for HPV-related diseases. Issue 6 (2nd June 2016) - Skeate, Joseph G.; Woodham, Andrew W.; Einstein, Mark H.; Da Silva, Diane M.; Kast, W. Martin
ABSTRACT: Carcinomas of the anogenital tract, in particular cervical cancer, remains one of the most common cancers in women, and represent the most frequent gynecological malignancies and the fourth leading cause of cancer death in women worldwide. Human papillomavirus (HPV)-induced lesions are immunologically distinct in that they express viral antigens, which are necessary to maintain the cancerous phenotype. The causal relationship between HPV infection and anogenital cancer has prompted substantial interest in the development of therapeutic vaccines against high-risk HPV types targeting the viral oncoproteins E6 and E7. This review will focus on the most recent clinical trials for immunotherapies for mucosal HPV-induced lesions as well as emerging therapeutic strategies that have been tested in pre-clinical models for HPV-induced diseases. Progress in peptide- and protein-based vaccines, DNA-based vaccines, viral/bacterial vector-based vaccines, immune checkpoint inhibition, immune response modifiers, and adoptive cell therapy for HPV will be discussed.